"Facing Our Fears": Using facilitated film viewings to engage communities in HIV research involving MSM in Kenya - Kombo, B; Sariola, S; Gichuru, E; Molyneux, S; Sanders, E; van der Elst, E (Cogent OA, 2017)
Kenya is a generally homophobic country where homosexuality is criminalised and people who engage in same sex sexuality face stigma and discrimination. In 2013, we developed a 16 min documentary entitled "Facing Our Fears" that aimed at sharing information on how and why men who have sex with men (MSM) are involved in on-going KEMRI HIV prevention research, and associated community engagement. To consider the film's usefulness as a communication tool, and its perceived security risks in case the film was publicly released, we conducted nine facilitated viewings with 122 individuals representing seven different stakeholder groups. The documentary was seen as a strong visual communication tool with potential to reduce stigma related to homosexuality, and facilitated film viewings were identified as platforms with potential to support open dialogue about HIV research involving MSM. Despite the potential, there were concerns over possible risks to LGBT communities and those working with them following public release. We opted-giving emphasis to the "do no harm" principle-to use the film only in facilitated settings where audience knowledge and attitudes can be carefully considered and discussed. The results highlight the importance of carefully assessing the range of possible impacts when using visuals in community engagement.